The optimization of micro propagation in almond (Prunus dulcis L.) in some genotypes/cultivars: To assess the effects of explant’s type and sterilization’s method on proliferation - Farzaneh Razavi; Masume Asadi Aghbolaghi (علوم و فناوری بذر ایران, 2024)
This study focused to optimize micropropagation in 11 different almond (Prunus dulcis)’s genotypes/cultivars. Main effort was to determine best explant and disinfection’s method in each genotype/cultivar. Almond’s cultivars, Mamaei (M), Shekoufeh (SH) and Fragnies (F) as well as bred almond lines; A1, A2, A3, A4, A5, A7, A8 and A9 were evaluated. The effect of explant; disinfection’s methods and genotype/cultivar were analyzed using factorial experiment on completely randomized design with 3 replications for each treatment. Results indicated 3 studied factors along with their interactions can greatly affect almond’s proliferation. The explant (woody/ herbaceous shoot) showed different effects on proliferation in different almond’s genotypes/cultivars. In genotype A1, herbaceous shoot showed not suitable proliferation (30.12) compared to woody one (40.20), while in genotype A7, herbaceous shoot resulted better (40.13) than woody shoot (36.20). Interestingly, in most studied genotypes/cultivars such as A1, A3, A8, A9, SH, M, and F, woody mature shoot exposed better proliferation. Likewise, sterilization’s method had different effects on proliferation in different genotypes/cultivars. For instance, sodium hypochlorite 25 % /15 (conc. (%)/min.) showed higher proliferation in A7, A8, A9 and F, whereas, in other genotypes/cultivars, using 50 %/10 (conc. (%)/min.) was superior. Results verified almond’s genotype/cultivar and its interaction with explant and disinfection’s method, can significantly affect on proliferation as a genetic related trait. Results indicated almomd’s genotype/cultivar, method of disinfection, type of explant (herbaceous or woody shoot) and their interaction can affect significantly on almond’s proliferation, growth’s performance and rate.